Effective Python LiveLessons (video training) - Slatkin, Brett (LiveLessons., 2015)
"Effective Python LiveLessons Video Training offers developers insight into the Pythonic way of writing programs, building on the viewer's fundamental understanding of Python to write programs more effectively. Based on Effective Python, the book written by Brett Slatkin for the Effective Software Development Series, each lesson contains a broad but related set of items. Each item is designed to provide concise and specific guidance on what to do and what to avoid when writing programs using Python. Hands-on demonstration helps the viewer understand how to put each item into action."--Resource description page.